INTEGRATING HADITH AND SCIENCE IN THE DIGITAL SPHERE: A Haughtian Analysis of Virtual Religious Content - Fauziyah, Farichatul; Lutfi, Muhammad; Zamzami, Mukhammad; Hegazy, Wael (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
This study analyzes how digital da‘wah constructs the relationship between hadith and science, applying John F. Haught’s typology as an analytical lens. As digital platforms increasingly shape the circulation of religious knowledge, the boundaries between revelation and scientific rationality become blurred, requiring closer attention to how authority is produced online. Through qualitative observations of several accounts on Instagram (@nurliya_alqurantulis), TikTok (@1menittojannah, @hadidjayatech, and @edimujiono19), and Facebook (Zulfa Khairi and Arie Elreal), this study shows that science functions less as an epistemic partner and more as a symbolic tool. The discourse loosely aligns with Haught’s confirmation and conflict models but does so superficially, using scientific references as legitimizing devices that reinforce scriptural authority rather than fostering meaningful dialogue. This shift, from a hermeneutical paradigm of ta’wil to a digital-verificative paradigm, suggests that religious truth is increasingly constructed through visual performance and rapid verification logics. The study’s contribution lies in the formulation of the concept of virtual scientific apologetics, namely a pattern of faith-defense within digital culture in which scientific symbols are mobilized to construct an image of religious modernity, thereby reducing the methodological autonomy of science. The concept enriches the epistemic transformation in contemporary Islamic digital discourses in Indonesia. It also offers a critical analysis of representational tendencies that reduce science to a mere instrument for legitimizing doctrine.